Rwandan maize market price dynamics: Structure, trends and policy implications - Warner, James; Benimana, Gilberthe Uwera; Mugabo, Serge; Niyonsingiza, Josue; Mukangabo, Emerence; Ingabire, Chantal (International Food Policy Research Institute, 2024)
The importance of maize for Rwanda cannot be overstated. Most smallholder farmers, along the spectrum of both land size and level of commercialization, engage in both production, own consumption, and sale of maize. Unlike most other crops, maize is commonly produced by all levels of commercialized and subsistence smallholder farmers. For example, recent research revealed that even though almost half of all maize produced is sold (44%), only an average of 23 percent is marketed at the household level (Warner et al. 2024). This indicates that while maize is widely sold by most smallholders, it is disproportionally sold by those with relatively larger farms. Therefore, maize is important for both own consumption as well as commercial sales and price movements are critical for understanding potential welfare impacts on both buyers and sellers. Research presented here outlines some important maize price relationships, including multi-year trends, interrelationships between Rwandan markets and seasonality. Overall, we find strong correlation between all markets suggesting a good degree of integration but persistent individual market prices above and below national averages as well as seasonality that generally conforms to maize’s main harvest period (Season A). This policy brief provides an overview of maize prices in Rwanda in order to enhance evidence-based policymaking for targeting recommendations aimed at more integrated and stable maize market prices throughout the country. For example, seasonal price changes suggest an annual average price fluctuation of approximately 30 percent and if targeted policies could reduce this seasonal price variation, smallholder welfare would likely be improved.